Potential regulatory molecules in the human trabecular meshwork of patients with glaucoma: Immunohistochemical profile of a number of inflammatory cytokines - TAURONE, SAMANTA; RIPANDELLI, GUIDO; PACELLA, ELENA; BIANCHI, ENRICA; PLATEROTI, ANDREA MARIA; DE VITO, STEFANIA; PLATEROTI, PASQUALE; GRIPPAUDO, FRANCESCA ROMANA; CAVALLOTTI, CARLO; ARTICO, MARCO (Molecular medicine reports, 2015)
Glaucoma occurs when there are imbalances between the production and the drainage of the eye liquid. The vast majority of the aqueous humor leaves the eye through the trabecular meshwork (TM). The cause of hypertonicity may be due to an alteration in the thickness of the TM. In the majority of cases the molecular changes that determine primary open-angle glaucoma (POAG) are unclear. However, it has been hypothesized that the significant increase in the extracellular matrix (ECM) of the fibrillary bands in the TM is associated with possible inflammatory conditions. In this study the tissue distribution of interleukin (IL)-6, IL-1β, transforming growth factor-β1 (TGF-β1), vascular endothelial growth factor (VEGF) and tumor necrosis factor α (TNF-α) was analyzed in TM samples from patients with POAG by immunohistochemistry. Seven specimens from patients with POAG and three control tissues were analyzed by immunohistochemistry using specific antibodies against these cytokines. Morphological changes in the TM, such as increased cell content, macrophages, fibrosis and accumulation of neutrophils, were observed by transmission electron microscopy. In human TM tissues, an evident immunoreactivity for IL-6, IL-1β and TNF-α was observed in patients with POAG when compared with the control subjects, indicating that these cytokines may be correlated with disease activity. TM endothelial cells secrete a number of factors and cytokines that modulate the functions of the cells and the ECM of the conventional outflow pathway. In the TM in glaucoma, macrophages produce cytokines, including IL-6, IL-1β and TNF-α, leading to an acute inflammatory response and recruitment of other immune cells, including T lymphocytes. In addition, TGF-β1 regulates and induces the expression of IL-6 in TM that indirectly induces angiogenesis by stimulating VEGF expression. The present results support previous evidence that suggests that growth factors and cytokines can induce ECM remodelling and alter cytoskeletal interactions in the TM.